Beam test performance of a prototype module with Short Strip ASICs for the CMS HL-LHC tracker upgrade. (1st June 2022) - ; Adam, W.; Bergauer, T.; Damanakis, K.; Dragicevic, M.; Frühwirth, R.; Steininger, H.; Beaumont, W.; Di Croce, D.; Janssen, X.; Kello, T.; Lelek, A.; et al.
Abstract: The Short Strip ASIC (SSA) is one of the four front-end chips designed for the upgrade of the CMS Outer Tracker for the High Luminosity LHC. Together with the Macro-Pixel ASIC (MPA) it will instrument modules containing a strip and a macro-pixel sensor stacked on top of each other. The SSA provides both full readout of the strip hit information when triggered, and, together with the MPA, correlated clusters called stubs from the two sensors for use by the CMS Level-1 (L1) trigger system. Results from the first prototype module consisting of a sensor and two SSA chips are presented. The prototype module has been characterized at the Fermilab Test Beam Facility using a 120 GeV proton beam.